Misalignment of productivity and wages across regions? Evidence from Belgian matched panel data - Rycx, François; Saks, Yves; Tojerow, Ilan (Bonn, 2016)
"This paper is one of the first to estimate how the region in which an establishment is located affects its productivity, wage cost and cost competitiveness (i.e. its productivity-wage gap). To do so, we use detailed linked employer-employee panel data for Belgium and rely on methodological approaches from both Hellerstein and Neumark (1995) and Bartolucci (2014) to estimate dynamic panel data models at the establishment level. Our findings show that interregional differences in productivity and wages are significant but vanish almost totally, both in industry and services, when controlling for a wide range of covariates, establishment fixed effects and endogeneity. Thus, our results suggest that wage cost and productivity differentials are ceteris paribus relatively well aligned across regions."